(untitled) (UNED Research Journal, 2018)
Ants have specific feeding preferences and daily activity cycles, but there are almost no data on tropical urban species. Through field collection and application of baits in Alajuela, Costa Rica, I obtained 902 records. I identified 15 urban ant species, with preference for certain foods, and daily cycles affected by food availability and the presence of dominant species.